Skrining Pemeriksaan Badan Keton Pada Urin Individu Obesitas Dengan Menggunakan Metode Gerhardt - Mutmainnah Abbas; Citra Annisa; Rosdiana Mus; Genevieva Esmeraldine Tanihatu; Dylan Tamalsir (PPNI UNIMMAN, 2024)
Obesity, or more commonly known as overweight, is an abnormal or excessive fat accumulation condition that can be harmful to health. This causes metabolic disorders such as insulin resistance, which causes carbohydrate metabolism to be disrupted, so the energy the body needs is produced by fatty acid metabolism. The fatty acid metabolism process produces the ketone body that occurs in the urine or ketonuria. This community dedication is aimed at screening ketone bodies tests in obese individuals in Puskesmas Antang, Kota Makassar. The respondents were 33 people with obesity who were willing to follow the activity. Based on the results of a study of 33 obese individuals, there were three positive urine ketones in comparison with 30 negative ones. Positive results indicate high levels of fatty acids that cause the presence of ketones in the urine. (Ketonuria).